Development of Peaceful Animation Video with Forgiveness in PAI Learning for Grade 6 Elementary School - Giscka Putri Berliana; Heti Sritindiani; Risma Nurul Rahmadina; Ani Nur Aeni (Prodi PGMI STIT Sunan Giri Bima, 2025)
Islamic Religious Education (PAI) in elementary schools (SD) plays a crucial role in shaping students' character from an early age. One of the key values in Islam is the attitude of forgiveness, which needs to be taught through engaging learning methods. This study measures the effectiveness of the Damaikan (Peace Through Forgiveness) animated video in enhancing students' understanding and practice of forgiveness. The research method used is Design & Development (D&D) with the ADDIE model. Data was collected through questionnaires, observations, and validation sheets at SDN Cinanggerang II, sixth grade. The validation results show that the animated video received a rating of 92.5% (excellent) from media experts and 78.7% (good) from subject matter experts, indicating its feasibility as a learning medium. Student questionnaires showed a positive response, with an average score of 79.6%. In conclusion, the Damaikan animated video is effective in increasing motivation for learning PAI and helping students understand and apply Islamic values, particularly in fostering a peaceful life through forgiveness.